1. The problem statement, all variables and given/known data Given, (y+2)dx + y(x+4)dy = 0, y(-3) = -1 2. Relevant equations v=y/x 3. The attempt at a solution I've been REALLY struggling with homogeneous equations for some reason...I just don't understand them all. so far i've tried two things. (1)dx -(y)dy ----- ------- (x+4) = (y+2) Not even sure what else to do from here. I tried getting dy/dx and got y+2 dy ---- = ----- y(x+4) dx Thanks in advanced for any assistance... I've been looking at this problem for hours and have other hw to get to.